2006
DOI: 10.1002/glia.20338
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline affects microglia activation, Aβ deposition, and behavior in APP‐tg mice

Abstract: Activated microglia and reactive astrocytes invade and surround cerebral b amyloid (Ab) plaques in Alzheimer's disease (AD), but the role of microglia in plaque development is still unclear. In this study, minocycline was administered for 3 months, prior to and early in Ab plaque formation in amyloid precursor protein transgenic mice (APP-tg). When minocycline was given to younger mice, there was a small but significant increase in Ab deposition in the hippocampus, concurrent with improved cognitive performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
143
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(156 citation statements)
references
References 31 publications
12
143
1
Order By: Relevance
“…In humans, long-term treatment with minocycline up to 200 mg/day is generally safe and well tolerated as In recent years, minocycline has been reported to have neuroprotective effects in various experimental neurodegenerative disease models such as cerebral ischemia (Yrjanheikki et al, 1999), traumatic brain injury (Sanchez Mejia et al, 2001), ALS (Zhu et al, 2002), PD (Wu et al, 2002), and HD (Chen et al, 2000;Wang et al, 2003). At present, a few number of studies are focused on the therapeutical potential of minocycline in AD (Hunter et al, 2004a;Seabrook et al, 2006), where it suppressed microglial production of IL-1beta, IL-6, TNF, and NGF in in vitro as well as APP transgenic mice (Seabrook et al, 2006). In addition, minocycline attenuated cholinergic cell loss, glial activation, and transcription of downstream pro-inflammatory mediators and mitigated the cognitive impairment, induced by mu p75-saporin, a novel immunotoxin that mimics the selective loss of basal forebrain cholinergic neurons and induces cognitive impairment in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, long-term treatment with minocycline up to 200 mg/day is generally safe and well tolerated as In recent years, minocycline has been reported to have neuroprotective effects in various experimental neurodegenerative disease models such as cerebral ischemia (Yrjanheikki et al, 1999), traumatic brain injury (Sanchez Mejia et al, 2001), ALS (Zhu et al, 2002), PD (Wu et al, 2002), and HD (Chen et al, 2000;Wang et al, 2003). At present, a few number of studies are focused on the therapeutical potential of minocycline in AD (Hunter et al, 2004a;Seabrook et al, 2006), where it suppressed microglial production of IL-1beta, IL-6, TNF, and NGF in in vitro as well as APP transgenic mice (Seabrook et al, 2006). In addition, minocycline attenuated cholinergic cell loss, glial activation, and transcription of downstream pro-inflammatory mediators and mitigated the cognitive impairment, induced by mu p75-saporin, a novel immunotoxin that mimics the selective loss of basal forebrain cholinergic neurons and induces cognitive impairment in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that minocycline treatment suppressed microglial production of IL-1beta, IL-6, TNF, and NGF in in vitro as well as amyloid precursor protein (APP) transgenic mice, but did not affect amyloid beta peptide (Ab) deposition in this Alzheimer's disease (AD) animal model (Seabrook et al, 2006). AD is one of the most popular neurodegenerative disorders characterized neuropathologically by the presence of neuritic plaques composed of amyloid fibrils and neurofibrillary tangles, which primarily contain paired helical filaments of hyperphosphorylated tau (Selkoe, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Minocycline is a lipid-soluble tetracycline that easily crosses the blood-brain barrier (Aronson, 1980) and has been documented to exert an inhibitory effect on A␤ fibril formation and microglial activation (Seabrook et al, 2006). The doses used in our experiments were selected according to a previous study carried out by Yrjänheikki et al (1999) who showed that they exert neuroprotective effects in global brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated that minocycline inhibits A␤-induced neuronal death and glial activation in the rat hippocampus (Ryu et al, 2004). Minocycline has also been reported to affect A␤ deposition and behavior in amyloid precursor protein transgenic mice and to improve cognition in young mice (Seabrook et al, 2006). In addition, Hunter et al (2004), using an experimental model of AD in mice, have documented that minocycline reduces the magnitude of cholinergic fiber loss in the hippocampus and attenuates cognitive impairment.…”
mentioning
confidence: 99%
“…Exenatide has now entered Phase II trials in 115 people with AD and MCI to establish the impact of treatment on cognition and AD biomarkers (NCT01255163-Jan2013). The antibiotic minocycline is also a promising candidate based on data from in vivo studies that show a direct impact on amyloid pathology and behaviour [14] and promising outcomes from open trials in Parkinson's disease [15]. The expert review also identified retinoid therapy as a potentially viable candidate for repositioning.…”
mentioning
confidence: 99%